TEKNOLOGI KONSERVASI LANSKAP GUMUK PASIR PANTAI PARANGTRITIS BANTUL DIY - Gunawan Budiyanto (http://arl.faperta.ipb.ac.id/, 2011)
Crescent sand dunes is one of the potential landscape of Parangtritis beach Bantul DIY, which has vista which is not owned by other beach attractions. Rows of sand dune that extends along the coast suffered erosion caused by wind-sea with north-west directions. This process resulted sand dune degradation and depositional process of sand particles to the land. One of wind erosion control is to use windbreaks to reducewind speed, to capture sand particles and deflect the wind direction. Windbreaks plant was conducted at two points. In the area of sand dune adjacent to coastline, as well as reducing wind speed and deflect wind direction, and the area behind the sand dune (backdune) with the aim capturing and holding the creep of sand particles.Sand dune conservation is becoming an important plan to be implemented. On the one hand, sand dune has the potential landscape which can still developed further, and on the other hand, sand dune can be a barrier savior of community behind these dunes. Parangtritis beach adjacent to the epicenter of the quake zone from both tectonic faults from Opak sesar and Indoaustralia-euroasia plate stretching in the southern island ofJava. Sustainability and stability of sand dune can reduce tsunami attack caused by earthquake.